Developing the Physical Fitness of Girls High Jumpers (Journal of Pedagogical Inventions and Practices, 2023)
This article deals with the results of control tests of the physical fitness of female high jumpers, aimed at improving the physical fitness of athletes, were obtained and analyzed.